2014
DOI: 10.17011/ht/urn.201411203311
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Response in Crisis: Individual and Collective Efforts to Enhance Community Resiliences

Abstract: This paper reports on the process and findings of an extensive research project with the aim of investigating present initiatives and approaches within the area of community resilience and citizen involvement. The paper specifically addresses which emerging sociotechnical approaches can be discerned within these initiatives. The discussion is structured within three categories of potential voluntary engagement; organized volunteers, semiorganized individuals, and "nonorganized" individuals. The empirical mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Even though, before and in the aftermath of emergency situation the support of social network is important for dealing with the disaster, at the disaster site the relationship between professionals and spontaneous, unorganized volunteers who are willing to help is ambivalent. Previous researches showed that volunteers might bring helpful contributions, but they also might be potential liabilities to the response activities (Barsky et al, 2007;Rivera and Wood, 2016;Linnell, 2014). Volunteers can participate in a variety of support activities on the sites of disasters, such as providing information, clearing debris, collecting food or providing shelter.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though, before and in the aftermath of emergency situation the support of social network is important for dealing with the disaster, at the disaster site the relationship between professionals and spontaneous, unorganized volunteers who are willing to help is ambivalent. Previous researches showed that volunteers might bring helpful contributions, but they also might be potential liabilities to the response activities (Barsky et al, 2007;Rivera and Wood, 2016;Linnell, 2014). Volunteers can participate in a variety of support activities on the sites of disasters, such as providing information, clearing debris, collecting food or providing shelter.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the growing number of crisis-related research, the focus is usually given to responses by authorities instead to empowering citizens [18]. Less attention has been given to bottom-up approaches, especially in the recovering phase [17], justifying the need of local communities not only as information providers but as actors therein [8]. Linnell [8] lists some conditions to promote citizen participation in community resilience, such as managing voluntarism and matching needs/skills/knowledge, reinforcing the culture of collaboration, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Less attention has been given to bottom-up approaches, especially in the recovering phase [17], justifying the need of local communities not only as information providers but as actors therein [8]. Linnell [8] lists some conditions to promote citizen participation in community resilience, such as managing voluntarism and matching needs/skills/knowledge, reinforcing the culture of collaboration, etc. In line with that, the framework in [4] suggests an approach focused on Engagement, Education, Empowerment and Encouragement (the 4 "Es").…”
Section: Introductionmentioning
confidence: 99%
“…;Ardalan (2013);Cretikos (2008);Falconi (2012); Jahangiri (2010);Kapucu (2008);Linnell (2014);McComas (2003);Mei (2013);Perry (2008); Tuerk (2013) AR; Al-Shahri (2014) AR;Al-Tuwairqi (2003) AR; Xie (2013) CH; FR; FR; FR; FR; FR; Gondard-Delacroix FR; FR;Rode (2008) FR;Setbon (2009) FR; Tamru (2002) FR; Vinet (2005) FR; Gabrichidze (2013) RU, Podkorytov (2014) RU QN-CG (GRADE): Moderate QN-DS (GRADE Adapted): Moderate to Low QL (CERQual): Moderate to Low MM, CS (as appropriate): Moderate Activities When leaders, with formal responsibilities related to emergencies, include community individuals (as planners and attendees) in preevent meetings for 1) plan/s development, 2) information dissemination, 3) training on who is responsible for what and what to do-social responsibility, 4) conducting preparedness actions, and 5) relationship bonding/building, there are increases in preparedness and response actions.Ardalan (2010); Ardalan (2013); Asharose (2015); Cretikos (2008); Falconi (2012); Jahangiri (2010); Karan (2007); McComas (2003); Mei (2013); Mitchell (2013); Perry (2008); Tuerk, (2013); Al-Sayed (2010) AR; Al-Shahri (2014) AR; Al-Tuwairqi (2003) AR; Ouda (2010) AR; Zahraan (2006) AR; Xie (2013) CH; Affletranger (2003) FR; Chahraoui (2003) FR; Duchêne (2004) FR; Gaillard (2002) FR; Gaillard (2008) FR; Gondard-Delacroix (2004) FR; Heitz (2013) FR; Kingdom of Morocco (2005) FR; Rode (2008) FR; Setbon (2009) FR; Tamru (2002) FR; Vinet (2005) FR; Gabrichidze (2013) public officials and experts help to build relationships of trust and confidence that transfers into coordination and social connectedness. High levels of trust (and similarly low levels of trust) may be associated with increased and/or decreased risk perception, participation in and satisfaction with activities, and preparedness/response actions.…”
mentioning
confidence: 99%